2016
DOI: 10.1121/1.4950847
|View full text |Cite
|
Sign up to set email alerts
|

The role of spectral detail in the binaural transfer function on perceived externalization in a reverberant environment

Abstract: Individual binaural room impulse responses (BRIRs) were recorded at a distance of 1.5 m for azimuth angles of 0 and 50 in a reverberant room. Spectral details were reduced in either the direct or the reverberant part of the BRIRs by averaging the magnitude responses with band-pass filters. For various filter bandwidths, the modified BRIRs were convolved with broadband noise and listeners judged the perceived position of the noise when virtualized over headphones. Only reductions in spectral details of the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(63 citation statements)
references
References 16 publications
(31 reference statements)
3
60
0
Order By: Relevance
“…A previous study in [17] investigated the role of spectral details in direct parts of BRIRs on perceived externalization. For that, different levels of smoothing were achieved by using gammatone filters with various bandwidth factors B (bandwidth factors are the values relative to one equivalent rectangular bandwidth (ERB) [25]) ranging from 0.316-63.1.…”
Section: Modification Of the Direct Part In The Brirmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study in [17] investigated the role of spectral details in direct parts of BRIRs on perceived externalization. For that, different levels of smoothing were achieved by using gammatone filters with various bandwidth factors B (bandwidth factors are the values relative to one equivalent rectangular bandwidth (ERB) [25]) ranging from 0.316-63.1.…”
Section: Modification Of the Direct Part In The Brirmentioning
confidence: 99%
“…Based on the two studies (cf. [8,17]) mentioned above, it could be concluded that the spectral details in the direct sound are important for perceived externalization of virtual sound sources when reverberation is present. However, relatively little is known about whether the spectral details in direct parts of ipsilateral and contralateral ear signals have the same influence on perceived externalization.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Individual BRIRs were measured from the loudspeakers placed at the azimuth angles of 0, 30, 150 180, 240, and 300 deg. The BRIR measurements were performed as described in Hassager et al (2016). The microphones were placed at the ear-canal entrances and were securely attached with strips of medical tape.…”
Section: Spatializationmentioning
confidence: 99%